Green Entrepreneurship: The Role of Sandwich Generation Intentions through Entrepreneurial Orientation and SDGs Literacy - Yanti, Tri Auri; Nurhadi, Aan; Rahman, Fauziyah; Lubis, Irna Triannur (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyse the role of the sandwich generation's intentions in shaping green entrepreneurship through entrepreneurial orientation and Sustainable Development Goals (SDGs) literacy in Deli Serdang Regency. The research approach used a quantitative method with a survey of the sandwich generation running micro and small businesses, and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results showed that entrepreneurial orientation and SDGs literacy had a significant influence on the formation of green entrepreneurship, while entrepreneurial intention acted as a mediator in strengthening this relationship. These findings emphasise the importance of developing entrepreneurial orientation and understanding of SDGs as strategies to encourage environmentally friendly business practices among the sandwich generation. This study provides practical implications for the government, educational institutions, and business actors in designing training and education programmes that support sustainable entrepreneurship.